The efficacy of a new translational treatment for persecutory delusions: study protocol for a randomised controlled trial (The Feeling Safe Study). Issue 1 (December 2016) - Freeman, Daniel; Waite, Felicity; Emsley, Richard; Kingdon, David; Davies, Linda; Fitzpatrick, Ray; Dunn, Graham
Abstract Background Persecutory delusions (strong unfounded fears that others intend harm to the person) occur in more than 70 % of the patients diagnosed with schizophrenia. This major psychotic experience is a key clinical target, for which substantial improvement in treatment is needed. Our aim is to use advances in theoretical understanding to develop a much more efficacious treatment that leads to recovery in at least 50 % of people with persistent persecutory delusions. Our cognitive conceptualisation is that persecutory delusions are threat beliefs, developed in the context of genetic and environmental risk, maintained by a number of psychological processes including excessive worry, low self-confidence, intolerance of anxious affect and other internal anomalous experiences, reasoning biases, and safety-seeking strategies. The clinical implication is that safety has to be relearned, by entering the feared situations after reduction of the influence of the maintenance factors. We have been individually evaluating modules targeting causal factors. These will now be tested together as a full treatment, called The Feeling Safe Programme. The treatment is modular, personalised, and includes patient preference. We will test whether the new treatment leads to greater recovery in persistent persecutory delusions, psychological well-being, and activity levels compared to befriending (that is, controlling for therapist attention). Methods/design The Feeling Safe Study is a parallel group randomised controlled trial for 150 patients who have persecutory delusions despite previous treatment in mental health services. Patients will be randomised (1:1 ratio) to The Feeling Safe Programme or befriending (both provided in 20 sessions over 6 months). Standard care will continue as usual. Online randomisation will use a permuted blocks algorithm, with randomly varying block size, stratified by therapist. Assessments, by a rater blind to allocation, will be conducted at 0, 6 (post treatment), and 12 months. The primary outcome is the level of delusional conviction at 6 months. Secondary outcomes include levels of psychological well-being, suicidal ideation, and activity. All main analyses will be intention-to-treat. The trial is funded by the NHS National Institute for Health Research. Discussion The Feeling Safe study will provide a Phase II evaluation of a new targeted translational psychological treatment for persecutory delusions. Trial registration Current Controlled TrialsISRCTN18705064 (registered 11 November 2015).